When planning the training of handball teams of university students, take into account the functional status of athletes by their temperament types - Abdueva Sitorabonu Savriddin qizi (Research Parks Publishers, 2021)
The article discusses the problems of improving the handball training of university student teams. It is emphasized that the success of a team in competitions depends in many ways on its ability to manage the mental state of each handball player. In this regard, the study of players ’temperament types as part of their psychological preparation helps to bring players to the highest level of readiness for competitions